Developing Block Chain Technology on Abcn Network Controller For Flyback Converter Fed Pv Grid in Modern Power System Using IOT - Madhavi Mallam; Siddalingesh Bandi; Sundresan Perumal; Kumutha Duraisamy; Sushma K Sattigeri; V.Devi priya (Geoscience Journal, 2026)
Non-Indexed Publication